Changes in PD-1 expression on T lymphocyte subsets and related immune indicators before and after definitive chemoradiotherapy for esophageal squamous cell carcinoma - Xueling Shi; Hongyu Zhao; Jiaqi Yu; Peng Cai; Shixiang Zhou; Ning Yang; Duojie Li (Annals of Medicine)
Objective This study aimed to observe the dynamic changes in the expression of T lymphocytes, natural killer (NK) cells, and PD-1 in patients with first-diagnosed esophageal squamous cell carcinoma (ESCC) before and after chemoradiotherapy (CRT) and evaluate the impact of PD-1 expression in peripheral blood on the short-term outcome of patients with ESCC.Patients and Methods Seventy-three patients with ESCC who were treated with definitive CRT were enrolled. Before and after CRT, flow cytometry was used to detect thePD-1 expression in the peripheral blood and related immune indicators. Peripheral blood from 10 healthy individuals was used as control.Results The percentages of CD3+ (p = 0.018), CD4+ (p < 0.001), and CD8+ T cells (p < 0.001); NK cells (p = 0.009); and the CD4+/CD8+ ratio (p < 0.001), as well as PD-1+CD3+ (p < 0.001), PD-1+CD4+ (p < 0.001), and PD-1+CD8+ (p < 0.001) T cells, before CRT significantly differed from those in the post-CRT group. The percentages of PD-1+CD8+ T cells differed significantly between the radiotherapy alone and CRT groups (p < 0.05). PD-1 expression in CD3+, CD4+, and CD8+ T cells significantly decreased in patients achieving overall response rate (all p < 0.05). Compared with those in the incomplete response group, PD-1+CD8+ T cells significantly decreased in the CR group (p < 0.05).Conclusion CRT aggravated immunosuppression and increased PD-1 expression in T lymphocyte subsets in patients with ESCC, possibly related to the radiation field. PD-1 expression in T lymphocyte subsets can predict short-term outcomes in patients and provide a theoretical basis for the sequential application of PD-1 immunosuppressants after radiotherapy and chemotherapy.